Pimecrolimus versus Placebo in Minor, Recurrent Aphthous Stomatitis: A Randomized Double-blind Controlled Trial - Ayda Moghaddas; Azadeh Moghaddas; AmirHossein Siadat; Giti Sadeghian (Research Center for Rational Use of Drugs (RCRUD), 2015)
Background: Oral aphthous is one of the most common oral mucosal inflammatory disorders which are very painful. There is no definite medical strategy up to now for aphthous treatment. Recently, some researchers have focused on immunomodulatory drugs such as tacrolimus and pimecrolimus in preventing aphthus recurrences. The aim of this study is to assess the effect of pimecrolimus cream against placebo in management of oral minor aphthous. Methods: The study is a randomized clinical trial, was done in "Shariati" hospital and Isfahan Skin Research Center. 62 patients with minor aphthuos were included and divided randomly to two groups (31 in each). In experimental group, pimecrolimus cream was applied for two weeks and cold cream for the same duration in control group. Patients were followed for 3 and one week; results were assessed in recovery after drug administration. Compared variables between two groups were including: the size of lesions, the time to recovery and pain intensity. Results: Results showed that mean size lesion in experimental and placebo group after complete recovery reduced (23.6 ±15.3 and 24.8 ±15 mm respectively) but it was not significant (P: 0.1). Mean time for recovery in both groups was 8±2.2 and 9.5±2.5 respectively which was significant in pimecrolimus treated patients (P: 0.014). Also mean degree for pain intensity measured by pain scale method was reduced significantly in test group (6 ± 1.2 before treatment and 5.3 ± 1.1 after treatment, P<0.001). Conclusion: This study stated that pimecrolimus cream has an appropriate effect in reduction of recovery time and pain in minor aphthous compared to placebo but more clinical studies are needed to better conclusion.